Effect of resistance exercise on physical fitness, quality of life, and fatigue in patients with cancer: a systematic review - Zhang, Qiuhua; Gao, Yanan; Wang, Wenjun; Zhao, Xiaoguang; Yu, Jiabin; Huang, Huiming (Frontiers in Oncology, 2024)
Objective The purpose of this study is to conduct a systematic review to assess the effects of different forms of resistance exercises (resistance exercise, resistance exercise combined with aerobic exercise, and resistance exercise combined with other exercises) on physical fitness, quality of life (QOL), and fatigue of patients with cancer. Methods We conducted a systematic review using the Cochrane Handbook for Systematic Reviews of Interventions guidelines. We searched PubMed, Web of Science, and Scopus databases for the studies from the establishment of the database to September 2023, including randomized controlled trials and clinical trials that evaluated the effects of different resistance exercise on physical fitness, QOL, and fatigue in all patients with cancer. Two reviewers independently assessed the quality of all the included studies using the Cochrane Handbook for Systematic Reviews of Interventions and MINORS scale. We divided the intervention into three types: resistance exercise, resistance exercise combined with aerobic exercise, and resistance exercise combined with other exercises. Results In total, 48 studies (3,843 participants) met the inclusion criteria. The three exercise intervention forms have significant effects on physical fitness and QOL, but the improvement effect on fatigue is not clear. A total of 34 studies reported significant and beneficial effects of resistance exercise on physical fitness across all types of cancer. There were 28 studies that reported significant or borderline improvement effects of resistance on QOL, and only 10 studies reported significant effects of resistance exercise interventions on fatigue improvement in patients with cancer. Conclusions Resistance exercise, resistance exercise combined with aerobic exercise, and resistance exercise combined with other exercises all have a positive effect on improving fitness and QOL in patients with cancer. Resistance exercise has an advantage in improving muscle strength, while combined resistance exercise has an advantage in improving QOL; however, there are no consistent findings in improving fatigue, although low-intensity resistance exercise is effective. Systematic review registration www.inplasy.com, identifier INPLASY2023110034.